STUDIES ON MOUSE LEUKEMIA : III. A COMPARISON OF FOUR LINES OF LEUKEMIA TRANSMITTED BY INOCULATION - Richter, Maurice N. (The Rockefeller University Press, 1930)
Several lines of lymphatic leukemia in mice, experimentally transmitted by inoculation into hosts of a closely inbred strain, have been established and carried on simultaneously. Among the inoculated mice there were found different types of response, according to the line of leukemia inoculated. The differences consisted mainly in the extent or distribution of lesions. Although the same line did not always show the same distribution of lesions, there was a distinct tendency for the cases in a line to present the same characteristics on successive transfers over a considerable period. A comparison of the frequency of the occurrence of certain lesions in four lines of transmission shows that: 1. Increases in the total leucocyte counts were less common and less marked in Lines A and E than in Lines H and I. In the lines first mentioned, normal counts were relatively frequent. In Line H normal counts were uncommon, and in Line I were not observed. The highest counts were found in Line I. 2. Peritoneal effusion was characteristic of Line A for 43 transfers. It was found in Line E, but for a considerably shorter period and in a smaller proportion of cases; it was rare in Lines H and I. 3. Pleural effusion was frequently found in Lines A and E but rarely in Lines H and I. 4. Infiltration in the liver occurred to a marked degree in all the mice of Lines H and I, but in fewer mice and to a variable degree in Lines A and E. 5. Infiltration in the kidney in Line I was present in 90 per cent of the mice, and was of marked grade. In line H it was present in 67 per cent of the mice (24 per cent of marked grade) but in Lines A and E it was rare. 6. A considerable amount of variability in results occurred in Lines A and E, whereas Lines H and I remained remarkably constant. The lesions characteristic of a line were not necessarily those present in the spontaneous case from which the first transfer of the line was made. As the mice used for inoculation were genetically uniform, the differences between the lines are not due to genetic differences in the hosts, but to differences in the materials inoculated.